2003
DOI: 10.1080/00016350310007590
|View full text |Cite
|
Sign up to set email alerts
|

Caries‐preventive effect of fluoride toothpaste: a systematic review

Abstract: With a questionnaire addressed to general dental practitioners in Sweden, the Swedish Council on Technology Assessment in Health Care launched a project group in 1999 to systematically review and evaluate the existing literature on various caries preventive methods. The aim of this article was to report findings concerning the caries preventive effect of fluoride toothpastes in various age groups, with special emphasis on fluoride concentration and supervised versus non-supervised brushing. A systematic search… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
183
1
17

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 259 publications
(209 citation statements)
references
References 31 publications
8
183
1
17
Order By: Relevance
“…The clinical efficacy of these toothpastes in deciduous teeth is a matter of dispute and particularly whether a lower caries preventive effect can be determined for fluoride concentration below 500 ppm. Twetman et al [15] stated in a recent review that inconclusive evidence was found regarding the effect of fluoride toothpaste in primary dentition. In contrast to our study, for permanent teeth Dunipace et al [7] and Wefel et al [16] found that mineral acquisition by initial white spot lesions increased with an increasing fluoride level.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical efficacy of these toothpastes in deciduous teeth is a matter of dispute and particularly whether a lower caries preventive effect can be determined for fluoride concentration below 500 ppm. Twetman et al [15] stated in a recent review that inconclusive evidence was found regarding the effect of fluoride toothpaste in primary dentition. In contrast to our study, for permanent teeth Dunipace et al [7] and Wefel et al [16] found that mineral acquisition by initial white spot lesions increased with an increasing fluoride level.…”
Section: Discussionmentioning
confidence: 99%
“…The authors, however, did not compare their findings with the systematic reviews by Twetman et al 5,6 in which both adults and children were considered. Twetman and colleagues 5 found limited evidence that fluoride mouthrinse prevented root caries in older adults.…”
Section: Commentarymentioning
confidence: 92%
“…Twetman and colleagues 5 found limited evidence that fluoride mouthrinse prevented root caries in older adults. Regarding fluoride toothpaste, all the studies of adult participants identified by Twetman et al 6 were dealing with materials or additional active ingredients other than fluoride. Therefore, none of these studies fulfilled the inclusion criteria and they were excluded.…”
Section: Commentarymentioning
confidence: 99%
“…Twetman et al 13 reported a strong evidence of caries preventive effect of daily use of fluoride toothpaste, but awareness regarding the role of fluoride was lacking among the study population. However majority of subjects were aware of the fact that smoking harms oral health.…”
Section: Awarenessmentioning
confidence: 99%